2021
DOI: 10.1038/s41550-021-01479-w
|View full text |Cite
|
Sign up to set email alerts
|

A radio technosignature search towards Proxima Centauri resulting in a signal of interest

Abstract: The detection of life beyond Earth is an ongoing scientific pursuit, with profound implications. One approach, known as the search for extraterrestrial intelligence (SETI), seeks to find engineered signals (‘technosignatures’) that indicate the existence of technologically capable life beyond Earth. Here, we report on the detection of a narrowband signal of interest at ~982 MHz, recorded during observations towards Proxima Centauri with the Parkes Murriyang radio telescope. This signal, BLC1, has characteristi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…The most publicised SETI event this year was certainly the Breakthrough Listen (BL) signal of interest blc1, producing three papers from the collaboration and many articles in the media. Smith et al (2021) described the BL search for radio technosignatures from the direction of Proxima Centauri using the Parkes Murriyang radio telescope and the detection of blc1. Its companion paper, Sheikh et al (2021a), presented the analysis of the technosignature candidate, which determined that the signal was not extraterrestrial, and instead produced by Earth-based electronics.…”
Section: Results From Searches (15 Papers)mentioning
confidence: 99%
“…The most publicised SETI event this year was certainly the Breakthrough Listen (BL) signal of interest blc1, producing three papers from the collaboration and many articles in the media. Smith et al (2021) described the BL search for radio technosignatures from the direction of Proxima Centauri using the Parkes Murriyang radio telescope and the detection of blc1. Its companion paper, Sheikh et al (2021a), presented the analysis of the technosignature candidate, which determined that the signal was not extraterrestrial, and instead produced by Earth-based electronics.…”
Section: Results From Searches (15 Papers)mentioning
confidence: 99%
“…The frequency resolution of the spectra is ∼7.5 Hz, and the integration time of each spectrum is 10 s. Each FITS file contains four polarization channels of two spectra recorded by one beam, and the total volume of our data is 66.5 TB (including calibration observations). The FITS files of one beam observing one target are concatenated and converted into two Filterbank files (XX and previous targeted SETI studies using turboSETI (Enriquez et al 2017;Price et al 2020;Sheikh et al 2020;Traas et al 2021;Gajjar et al 2021;Smith et al 2021), we adopt the most commonly used values for these parameters, setting the S/N threshold to 10 and the MDR to 4 Hz s −1 . Too high or too low S/N threshold will lead to too few or too many events.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, targeted SETI observations have become prevalent due to the discoveries of more and more exoplanets (Dressing & Charbonneau 2013;Petigura et al 2013;Batalha 2014). Since 2017, the Breakthrough Listen initiative has conducted a series of targeted SETI observations using the Green Bank Telescope (GBT) and the Parkes radio telescope (Parkes), whose targets have involved nearby stars (Enriquez et al 2017;Price et al 2020;Sheikh et al 2020), discovered exoplanets (Traas et al 2021;Smith et al 2021), and the Galactic Center (Gajjar et al 2021). However, although massive efforts have been made, no conclusive evidence of the existence of extraterrestrial intelligence (ETI) has been found so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar searches for extraterrestrial intelligence (SETI) are being carried out in high-time resolution data sets (Lacki et al 2021). Very recently, the Parkes Breakthrough Listen observations detected a suspicious signal ('blc1') at around 982 MHz towards Proxima Centauri (Smith et al 2021), which turned out to have terrestrial origin after detailed analysis (Sheikh et al 2021).…”
Section: Introductionmentioning
confidence: 99%